Lean Construction for BIM Asset Management in Healthcare Facilities: a Systematic Literature Review - Dulanto Cam, Gianmarco Rodrigo (2025)
Building Information Modeling (BIM) has become a transformative tool for managing facility assets across their lifecycle. In Healthcare Facilities (HF), its integration into Asset Management (AM) offers potential benefits, including operational efficiency, cost reduction, and enhanced patient safety. However, implementing BIM AM in HF remains challenging due to issues related to interoperability and data, organizational and procedural barriers, limited expertise, and resource demands. This study conducts a systematic literature review (SLR) to examine how Lean Construction principles can be integrated into BIM AM practices to address these barriers. A total of 23 peer-reviewed studies were analyzed from the Scopus and IGLC.net databases. The findings reveal that Lean principles enhance BIM AM by improving interoperability, enabling incremental data exchange, and supporting real-time decision-making. Collaborative planning frameworks, post-occupancy evaluations, and early FM involvement further align organizational workflows with lifecycle needs. Additionally, simplified modeling strategies and training initiatives address expertise gaps and resource constraints. The study contributes to the integration of Lean into BIM AM, offering practical insights for optimizing cost efficiency, operational adaptability, and long-term performance of AM in HF.